Chemical Coupled PEDOT:PSS/Si Electrode: Suppressed Electrolyte Consumption Enables Long-Term Stability - Liu, Xuejiao; Xu, Zhixin; Iqbal, Asma; Chen, Ming; Ali, Nazakat; Low, CheeTongJohn; Qi, Rongrong; Zai, Jiantao; Qian, Xuefeng (Nano-Micro Letters, 2021)
Huge volume changes of Si during lithiation/delithiation lead to regeneration of solid-electrolyte interphase (SEI) and consume electrolyte. In this article, γ-glycidoxypropyl trimethoxysilane (GOPS) was incorporated in Si/PEDOT:PSS electrodes to construct a flexible and conductive artificial SEI, effectively suppressing the consumption of electrolyte. The optimized electrode can maintain 1000 mAh g−1 for nearly 800 cycles under limited electrolyte compared with 40 cycles of the electrodes without GOPS. Also, the optimized electrode exhibits excellent rate capability. The use of GOPS greatly improves the interface compatibility between Si and PEDOT:PSS. XPS Ar+ etching depth analysis proved that the addition of GOPS is conducive to forming a more stable SEI. A full battery assembled with NCM 523 cathode delivers a high energy density of 520 Wh kg−1, offering good stability. Highlights: 1 γ-Glycidoxypropyl trimethoxysilane (GOPS) was incorporated in Si/PEDOT:PSS electrodes to construct a flexible and conductive artificial solid-electrolyte interphase (SEI). 2 XPS Ar+ etching depth analysis proved that the addition of GOPS is conducive to forming a more stable SEI. 3 A full battery assembled with NCM 523 cathode delivers a high energy density of 520 Wh kg-1, offering good stability.